Cerebral Microbleeds Are Associated With Increased Brain Iron and Cognitive Impairment in Patients With Cerebral Small Vessel Disease: A Quantitative Susceptibility Mapping Study. Issue 3 (31st January 2022) - Li, Jing; Nguyen, Thanh D.; Zhang, Qihao; Guo, Lingfei; Wang, Yi
Abstract : Background: Cerebral microbleeds (CMBs) have been recognized to play an important role in cognitive impairment of cerebral small vessel disease (CSVD) patients. However, the mechanism of this effect is still unclear. Purpose: Comparing the susceptibility values in the selected subcortical gray matter structures of CSVD patients without CMBs (CSVD‐N) and with CMBs (CSVD‐C) as well as healthy controls (HCs). Study Type: Prospective. Subjects: Sixty‐nine CSVD patients and 28 HCs were included; 24 CSVD patients (34.78%) had CMBs and 45 CSVD patients (65.22%) had no CMBs. Field Strength/Sequence: All subjects were imaged on a 3.0 T MR scanner. The protocol consisted of a three‐dimensional (3D) T1‐weighted sequence and a 3D multi‐echo gradient echo (mGRE) sequence. Brain QSM maps were computed from mGRE data using the morphology‐enabled dipole inversion with automatic uniform cerebrospinal fluid zero reference algorithm (MEDI+0). Assessment: The mean susceptibility value within each region of interest was recorded. All participants underwent the cognitive assessment. Brain iron deposition burden of CMB lesions of every CSVD‐C patient was computed. Statistical Tests: One‐way analysis of variance test followed by Tukey's honest significance test and Kruskal–Wallis test were used with significance level of 0.05. Stepwise multivariate linear analysis was used to explore the factors influencing cognitive scores. Results: Montreal cognitive assessment (MoCA), trail‐making test (TMT)‐A and TMT‐B scores in the three groups were significantly different (all P  < 0.05). Stepwise multivariate linear regression analysis revealed that the factors influenced MoCA scores were having CMBs ( P  < 0.05), white matter hyperintensities ( P  < 0.05), lacunes ( P  < 0.05) in brain, and the brain iron deposition burden of CMB lesions ( P  < 0.05) and for TMT scores (TMT‐A + TMT‐B), the influencing factors were age ( P  < 0.05), education years ( P  < 0.05), and the brain iron deposition burden of CMB lesions ( P  < 0.05). Data Conclusion: The higher iron deposition burden of CMB lesions in brain may be an imaging quantitative marker of cognitive decline in patients with CSVD‐C. Level of Evidence: 1 Technical Efficacy: Stage 2